2021
DOI: 10.48550/arxiv.2108.10463
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Semiclassical measures for higher dimensional quantum cat maps

Abstract: Consider a quantum cat map M associated to a matrix A ∈ Sp(2n, Z), which is a common toy model in quantum chaos. We show that the mass of eigenfunctions of M on any nonempty open set in the position-frequency space satisfies a lower bound which is uniform in the semiclassical limit, under two assumptions:(1) there is a unique simple eigenvalue of A of largest absolute value and (2) the characteristic polynomial of A is irreducible over the rationals. This is similar to previous work [DJ18, DJN19] on negatively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…We finally discuss the quantum cat map analog of the higher-dimensional Conjecture 4.5, by considering quantum cat maps associated to symplectic integer matrices A ∈ Sp(2n, Z). In this setting Dyatlov-Jézéquel [DJ21] proved Theorem 8. Let µ be a semiclassical measure for a quantum cat map associated to a matrix A ∈ Sp(2n, Z) such that:…”
Section: Quantum Cat Mapsmentioning
confidence: 88%
See 1 more Smart Citation
“…We finally discuss the quantum cat map analog of the higher-dimensional Conjecture 4.5, by considering quantum cat maps associated to symplectic integer matrices A ∈ Sp(2n, Z). In this setting Dyatlov-Jézéquel [DJ21] proved Theorem 8. Let µ be a semiclassical measure for a quantum cat map associated to a matrix A ∈ Sp(2n, Z) such that:…”
Section: Quantum Cat Mapsmentioning
confidence: 88%
“…See Figure 1 for a numerical illustration. In particular, we will describe full support statements for weak limits -see Theorem 4 and Theorem 8 -proved in [DJ18,DJN21,DJ21]. The key component is the fractal uncertainty principle first introduced by Dyatlov-Zahl [DZ16] and proved by Bourgain-Dyatlov [BD18].…”
Section: Introductionmentioning
confidence: 99%
“…We review the pseudodifferential calculus on H N , which also may be found in [3], [8], [19]. Let a ∈ C ∞ (T 2 ).…”
Section: The Propertymentioning
confidence: 99%
“…Most results from pseudodifferential calculus carry over to H N , see [3], [8] for details. In particular, there is an analogue of Lemma 2.1, given as follows.…”
Section: The Propertymentioning
confidence: 99%
See 1 more Smart Citation